2019
DOI: 10.11591/ijphs.v8i2.17930
|View full text |Cite
|
Sign up to set email alerts
|

Black cumin seed oil increase leucocyte and CD4Thelper number in sprague-dawley rats induced with dimethylbenzanthracene

Abstract: <p>Cigarette smoke contains 7, 12 dimethylbenzanthracene (DMBA). Metabolic of DMBA is immunosuppressive. Black cumin seed oil (BCSO) is an immunomodulation. The aim of this study was to determine the effect of BCSO on leukocyte, CD4Th and CD4CD25Treg in Sprague-Dawley (SD) mice induced with DMBA. The 96 SD rats were divided into 8 groups of 12. Group I received aquabidest and standard feeding. Groups II, III and IV received BCSO (an equivalent of 6.8, 68 and 136 mg/kg BW / day thymoquinone, respectively)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
1
8
0
2
Order By: Relevance
“…The present study revealed signi cant promotion in the levels of IF-γ, IL-12 and TNF-α in Sa30 and Sa50 groups that seemed to be dose dependent. Present data were in harmony with Gholamnezhad et al 107 , Aljabre et al 108 , Gholamnezhad et al 109 and Titiek et al 110 . These results explained the cell mediated immunostimulatory effect of Nigella sativa where IL-12 enhanced IF-γ that acted in autocrine and paracrine manner to increase CD8 cells activity.…”
Section: Discussionsupporting
confidence: 89%
“…The present study revealed signi cant promotion in the levels of IF-γ, IL-12 and TNF-α in Sa30 and Sa50 groups that seemed to be dose dependent. Present data were in harmony with Gholamnezhad et al 107 , Aljabre et al 108 , Gholamnezhad et al 109 and Titiek et al 110 . These results explained the cell mediated immunostimulatory effect of Nigella sativa where IL-12 enhanced IF-γ that acted in autocrine and paracrine manner to increase CD8 cells activity.…”
Section: Discussionsupporting
confidence: 89%
“…Minyak jintan hitam juga diketahui mampu meningkatkan respon imun selular yang ditandai dengan peningkatan jumlah sel T helper (CD4) pada konsentrasi 6,8 mg/kg BB/hari (Hidayati et al, 2019). Disisi lain, jintan hitam diketahui potensial untuk memodulasi sistem imun sehingga mengurangi terjadinya badai sitokin pada pasien Covid-19 dengan penghambatan IL-1, IL-6, IL-10, IL-18, TNF-α, and NF-κB (Kulyar et al, 2021).…”
Section: Bijiunclassified
“…Phase I clinical trial results have been shown that the administration of BCSO for 21 days to 36 healthy volunteers does not affect kidney function [20]. Nigella sativa L. provides a protective effect and useful for preventing kidney failure [21], antidiabetogenic [22], antioxidant [2], chemoprevention [23], and immunomodulatory agent [24].BCSO preparations are thought to affect TNF-α levels and creatinine levels in patients at risk of MS with standard therapy.…”
Section: Introductionmentioning
confidence: 99%